2003
DOI: 10.1128/aem.69.10.5870-5874.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Fumonisin B1Increases Intestinal Colonization by PathogenicEscherichia coliin Pigs

Abstract: Fumonisin B 1 (FB 1 ) is a mycotoxin that commonly occurs in maize. FB 1 causes a variety of toxic effects in different animal species and has been implicated as a contributing factor of esophageal cancers in humans. In the present study, we examined the effect of dietary exposure to FB 1 on intestinal colonization by pathogenic Escherichia coli associated with extraintestinal infection. Three-week-old weaned pigs were given FB 1 by gavage as a crude extract or as a purified toxin at a dose of 0.5 mg/kg of bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
90
2
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 55 publications
6
90
2
8
Order By: Relevance
“…It was also found that FB 1 given at diet levels of 10 ppm, has immunosuppressive effect on humoral immune response in pigs (Stoev et al, 2012) and therefore can provoke some secondary bacterial infections, which arise in immunocompromised animals. In this regard, Oswald and collaborators observed a significant increase of intestinal colonization of pathogenic Escherichia coli in FB 1 -treated pigs (Oswald et al, 2003). On the other hand, a heavy progression of Pasteurella multocida (Halloy et al, 2005) or porcine reproductive and respiratory syndrome (PRRS) virus infections in swine (Ramos et al, 2010) were seen when the same animals were compromised by feed exposure to FB 1 .…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that FB 1 given at diet levels of 10 ppm, has immunosuppressive effect on humoral immune response in pigs (Stoev et al, 2012) and therefore can provoke some secondary bacterial infections, which arise in immunocompromised animals. In this regard, Oswald and collaborators observed a significant increase of intestinal colonization of pathogenic Escherichia coli in FB 1 -treated pigs (Oswald et al, 2003). On the other hand, a heavy progression of Pasteurella multocida (Halloy et al, 2005) or porcine reproductive and respiratory syndrome (PRRS) virus infections in swine (Ramos et al, 2010) were seen when the same animals were compromised by feed exposure to FB 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxin (AFL), a hepatoxin, is produced by Aspergillus flavus and causes reduction in daily gain of chicken and egg shell weight (Zaghini et al 2005). Fumonisin (FUM) which is produced by Fusarium moniliforme, is often found as a contaminant in corn and causes reduction of egg production in quail (Butkeraitis et al 2004) and feed intake in calves (Mathur et al 2001), as well as increases colonization of pathogenic Escherichia coli in the small and large intestines of pig (Oswald et al 2003). Ochratoxin (OCRA) which is produced by Aspergillus ochraceus, causes mortality in chicks or broiler chicken (Gibson et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins have also been reported to affect the extrinsic components of intestinal immunity. While the effects on secretion of immunoglobulin [18][19][20] and expression of chemokines and cytokines [21][22][23][24][25] have been reported in several studies, their effects on mucus and antimicrobial peptide synthesis and secretion are poorly documented. Recently, our data clearly demonstrated the effects of individual and mixtures of Fusarium toxins on endpoints including antimicrobial peptides [26] and pro-inflammatory cytokines [27].…”
mentioning
confidence: 99%